EPISTEMOLOGI PENAFSIRAN KEPEMIMPINAN POLITIK PEREMPUAN DALAM ISLAM: (Studi Komparasi) - Adam Mustakim (Fakultas Ushuluddin, Adab dan Dakwah, Universitas Islam Negeri (UIN) Datokarama Palu, Indonesia, 2018)
Discussions about women, especially the perspective of the Qur'an and Hadith, seemed to never stop to be discussed. Many assumptions behind these issues, among the most fundamental issues are patriarchal phenomena. The tendency for this phenomenon ultimately results in a reflection on all levels of human life, among politically, culturally, sociologically, and institutionally. In fact, it is not uncommon to assume that the issue of patriarchy has strong theological legitimacy.